Dilemmas related to the concept and valuation of intangible assets in the accounting system of an enterprise - Bąk, Melania (Dylematy związane z pojęciem i wyceną wartości niematerialnych w systemie rachunkowości przedsiębiorstwa, 2011)
A part of intangible property is presented in an accounting system and its valuation conforms to generally accepted regulations, while a significant part of an enterprise’s intangible property does not meet conditions defined by legal regulations and cannot be presented in an accounting system. Commonly accepted valuation methods are also missing for this part of intangible property. In many cases defining value means, in fact, its estimation. Valuation issues are closely related to the concept of intangible property, which, by research environment and actual practitioners, is differently defined. In some cases the terms are used interchangeably, which results in certain ambiguity regarding what is actually valuated (intangible property as intangible assets presented in balance sheet, or intangible property as intellectual capital)
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 115-132
Keywords: accounting system; valuation; intangible property